Trends in biomaterials for three dimensional cancer modeling - Caballero, David (2020)
During the last decade, the type of biological assays that are used for extracting information about the efficiency of drugs (including cancer-related compounds) have dramatically changed. The reason is that a large amount of these drugs fail when they are tested in preclinical assays. This is because most pre-clinical drug evaluations rely on simplified in vitro assays based on flat two-dimensional (2D) surfaces. This type of assay poorly correlates with the human disease state. Therein, the cells display artificial phenotypes and perturbed gene expressions. In general, the drugs respond differently than in vivo. Ex vivo (e.g., biopsies) and in vivo (e.g., animal) models are also employed for drug evaluation. In cancer research, these models display certain advantages over 2D surfaces, such as a greater biological complexity. This makes the drugs to produce native-like responses. However, ex vivo models typically lack perfusion and are not representative of the heterogeneity of the tumor. In contrast, in vivo (animal) models are highly dynamic systems, but they are very costly, lack the human immune system, and are ethically controversial. In addition, regardless of the type of animal model, it is extremely difficult to investigate cellular and physiological interactions on this type of models. More advanced tumor models are patient-derived xenografts, where a surgically resected tumor sample of a patient is engrafted into an immunodeficient mice. However, these models are extremely expensive and time-consuming, they are associated with ethical concerns, and individual parameters cannot be isolated.